Role of Translations in Sci-Tech Libraries, 1st edition - Mount, Ellis (Routledge, 2020)
This book, first published in 1983, examines translation sources and their activities, as well as ways in which librarians can become aware of what has been translated, and obtain copies. The sci-tech literature of the world reflects the international nature of its sources, and is published in many languages. There are many avenues available for obtaining translations of such materials, and this book is devoted to a review of these sources and their activities.